Perlindungan Hukum Bagi Konsumen dari Peredaran Makanan Kedaluwarsa - Erfan M; Johamran Pransisto; Muh. Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to determine the form of legal protection for consumers against the circulation of expired food in Enrekang Regency and to find out the efforts made by the Government and the community in preventing the circulation of expired food in Enrekang Regency. secondary. The results of the study show that the form of legal protection for consumers of expired food products, especially in Enrekang District, Enrekang Regency, is the existence of a prohibition for business actors as regulated in Article 8 letter g paragraph (2) and paragraph (4). Apart from that, the form of legal protection for consumers is also contained in Article 7 of the UUPK which regulates the obligations of business actors, the form of legal protection can also be seen in Article 19 of the UUPK which regulates the responsibilities of business actors and the efforts made by the Government together with the community in preventing the distribution of expired food. in Enrekang District, Enrekang Regency, namely with the Government's responsibility to provide guidance to business actors and carry out joint supervision of Non-Governmental Organizations engaged in Consumer Protection by carrying out market operations or raids on cake shops and Mini Markets.